Long-term benefits from investing in international real estate - Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper analyses long- and short-term co-movements between 14 international real estate stock markets based on bivariate testing for cointegration and correlation analysis. The results indicate that there exist strong long-term relationships within economic and geographical regions, but less long-run linkages between real estate markets in different continents. Thus, investors would benefit from broadening their investment horizon from their domestic continent to Australia, Europe, and Northern America. Furthermore, it is shown that within each region there are one or two key markets influencing neighbouring markets like Australia in the Asia-Pacific region, the U.S. in the Anglo-Saxon area, and France and the Netherlands in the EMU. Therefore it is implied, from an investor's point of view, that it should be sufficient to focus only on these central markets. With respect to the efficient market hypothesis, the findings by cointegration analysis put some further doubt on its validity for securitized real estate markets.
Keywords: C22; G11; G14; 330; Cointegration; Correlation Analysis; Diversification; Securitized Real Estate Markets; Börsenkurs; Immobilienfonds; Immobilienmarkt; Securitization; Internationaler Preiszusammenhang; Korrelation; Industriestaaten; Welt